Short-Term Memory of the Amplitude of Body Rotation in Orienting Behavior of African Clawed Frog (Xenopus laevis). (26th March 2013) - Okazawa, Gouki; Funahashi, Shintaro
Abstract : African clawed frog ( Xenopus laevis ) can orient its body toward the prey by analyzing the direction of approaching water waves. Xenopus accurately orients toward the source of the stimulus when the stimulus is generated several cm away from its body. However, although Xenopus orientation behavior fluctuates when the stimulus is generated very near or above its body, the amplitude of the body rotation in the orienting behavior was affected by the preceding orienting behavior that had been performed several seconds before. In particular, the amplitude of the rotation in response to the stimulus applied above the body was positively correlated with that of the preceding rotation behavior in response to a stimulus generated several cm away from the body, indicating that Xenopus tends to repeat the preceding behavior if the direction of the stimulus is ambiguous. The results presented show the evidence that Xenopus can retain the amplitude of the rotation of the preceding orienting behavior for several seconds.